The Use of Virtual Reality (VR) as a Learning Media to Improve the Virtual Tour Experience in the Sharia Tourism Study Programme - Agnes Fransiska Dewi; Andi Nurindah Sari; Muhammad Shaleh Assingkily (Yayasan Zia Salsabila, 2024)
Various findings and utilisation of virtual reality (VR) technology are clear evidence of the existence of technology as a digital era learning media. However, the use of VR in the world of tourism is considered irrelevant because tourism must be a direct visit. This research aims to improve the virtual tour experience in sharia tourism study programme students using VR. This is based on cost efficiency, time constraints, permits, security and others if the tour is a direct visit. To obtain data, qualitative research with descriptive study methods is used. Various phenomena in the field will be collected through interviews, observations, and documentation studies. Finally, the data is analysed using data reduction, data display, and conclusion drawing, and tested for validity through data triangulation. This research shows that VR in tourism has a significant positive impact, especially in the context of education and enhancing the virtual tour experience and preparing students to face the demands of the modern tourism industry in the era of society 5.0, as well as supporting the steps of study programmes and faculties in adopting the latest educational technology as well as a reference for lecturers for technological developments relevant to study programmes, especially the Sharia Tourism Study Program.